Terapi Seni Pada Pasien Anak dengan Kanker : Literatur Review - Harisandy, Alvian; Rosadi, Erik; Afdhal, Fitri; Subantara, Dandi Oka; Sari, Anggia Prima (JURNAL KESEHATAN TERAPAN, 2024)
Children with cancer will face physical, psychological, social and spiritual problems and can lead to death throughout the course of the disease. Implementing art therapy interventions into the holistic care of pediatric oncology patients can help maximize quality of life and obtain appropriate means of communication. The aim of this literature review is to determine the effectiveness of art therapy in pediatric cancer patients. The method used is a literature review using the Google Scholar Proquest, Science Direct and Pubmed databases. The research results showed that from the 6 articles there were 3 themes of art therapy, namely expressive writing, drawing, and bibliotherapy, which generally had a positive impact on the patient's health well-being and improved quality of life. In conclusion, more research is needed on art therapy in cancer patients, especially in pediatric cancer, so that art therapy becomes a new and efficient supportive intervention in routine practice that is easy to apply without harm and side effects in pediatric patients with cancer.